Pengaruh Kebiasaan Membaca Komik Digital di Platform Line Webtoon terhadap Kemampuan Critical Reading Pada Generasi Z - Putri, Salsabila; Wenny, Lili Sudria (Syarif Hidayatullah State Islamic University of Jakarta, 2024)
In a digital age marked by the popularity of online platforms such as Line Webtoon among Generation Z, the influence of digital comic reading habits on critical reading skills is becoming increasingly relevant. This study aims to determine how much the habit of reading digital comics on the Line Webtoon platform influences vital reading ability in Generation Z. The research method used is quantitative explanative. Data analysis using simple linear regression tests, coefficients of determination, and correlation analysis with the help of SPSS V21 software. Data were collected by using questionnaires to 100 respondents of digital comic readers at Line Webtoon aged 18-24 years with an accidental sampling technique. The results showed a positive relationship between the habit of reading digital comics on Line Webtoon and critical reading skills in Generation Z, with a correlation value of 0.697 along with a significance value of 0.000. The results of R Square show that the habit of reading digital comics on Line Webtoon influences critical reading ability in Generation Z by 0.486 or 48.6%. The magnitude of the influence includes the range of coefficient intervals 0.40 – 0.599 (medium). This shows that the habit of reading digital comics on the Line Webtoon platform has a moderate and significant influence on critical reading skills in Generation Z.